Male Turkey Performance (Meleagris gallopavo) Ages 24 – 29 Weeks Given Rations Contain Turmeric Flour (Curcuma domestica Val.) - Idhar, Idhar; Hatta, Ummiani (AgriSains, 2020)
This study aims to test the best substitution level of turmeric flour in rations on the growth performance of male turkeys aged 24-29 weeks in the experimental cage of the Faculty of Animal Husbandry and Fisheries, University of Tadulako which is located in Sibalaya Village, Tanambulava District, Sigi Regency for 5 weeks. This study was designed using a completely randomized design (CRD), namely R0 = without + turmeric flour in the ration (control), R1 = 99.5% control ration + 0.5% turmeric flour, R2 = 99.5% control ration + 1 % turmeric flour, R3 = 99.5% control ration + 1.5% turmeric flour. The research variables were ration consumption, body weight gain, and ration conversion. The results showed that using turmeric flour as a feed additive had no significant effect on ration consumption, body weight gain, and ration conversion for male turkeys aged 24-29 weeks.